Respostas
respondido por:
2
a2 = 4
a3 = 6
Termo Geral da PA:
an = a1 + (n - 1).r
a3 = a1 + (3-1)r
a3 = a1 + 2r
Para encontrar a razão, basta subtrair:
r = a3 - a2
r = a3 - a2
r = 6 - 4
r = 2
a2 = a1 + r
a2 - r = a1
4 - 2 = a1
2 = a1
a1 = 2
a4 = a3 + r
a4 = 6 + 2
a4 = 8
PA: (2,4,6,8)
a3 = 6
Termo Geral da PA:
an = a1 + (n - 1).r
a3 = a1 + (3-1)r
a3 = a1 + 2r
Para encontrar a razão, basta subtrair:
r = a3 - a2
r = a3 - a2
r = 6 - 4
r = 2
a2 = a1 + r
a2 - r = a1
4 - 2 = a1
2 = a1
a1 = 2
a4 = a3 + r
a4 = 6 + 2
a4 = 8
PA: (2,4,6,8)
poxaina:
Obrigada
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás